2020
DOI: 10.1093/europace/euaa001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of Watchman vs. Amplatzer occluders for left atrial appendage closure (WATCH at LAAC)

Abstract: Aims This study compares clinical outcomes of Watchman vs. Amplatzer devices for left atrial appendage closure (LAAC). Methods and results Of two real-world registries, the Watchman registry Lichtenfels, Germany, and the Amplatzer registry Bern-Zurich, Switzerland, 303 and 333 consecutive patients, respectively, were included. After a 1:1 propensity score matching, 266 vs. 266 patients were compared by use of the predefined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
8
22
1
Order By: Relevance
“…The authors evaluated the long-term efficacy of LAAO procedure in primary and secondary stroke prevention and reported comparable efficacy outcome during a mean follow-up of 50 months. The 6.2% rate of TIA/stroke in the WD group, observed in our study, correlated well with data from the PREVAIL trial (6.4%) [ 16 ] and the aforementioned European registries (6.4%) [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors evaluated the long-term efficacy of LAAO procedure in primary and secondary stroke prevention and reported comparable efficacy outcome during a mean follow-up of 50 months. The 6.2% rate of TIA/stroke in the WD group, observed in our study, correlated well with data from the PREVAIL trial (6.4%) [ 16 ] and the aforementioned European registries (6.4%) [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no major adverse events occurred in the WD group, which correlated well with data from the EWOLUTION registry [ 13 ]. The analysis of two European real-world registry data, performed by Kleinecke et al [ 14 ] reported a comparable periprocedural major complications rate for the WD and Amplatzer group devices (4.1% vs. 6.0%, p = 0.32). A recent meta-analysis of six studies also confirmed the comparable safety outcomes for the WD and Amplatzer groups [ 15 ].…”
Section: Discussionmentioning
confidence: 97%
“…13-16, 29,31 However, only few retrospective data reported a head-to-head comparison of clinical outcomes of Amplatzer and Watchman devices and especially industry-independent data are lacking. [23][24][25][26][27][28] In our real-world study, the incidence rate of periprocedural MACCE for our cohort was 6.6%, with an incidence of 2.7% in the Watchman group and 10.6% in the Amulet group. In the previously published Watchman studies, the rates of 7-day procedure-related serious adverse events were 8.7% in PROTECT-AF trial, 4.2% in the PREVAIL trial, and 2.8% in the EWOLUTION study.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the Amulet IDE and Wavecrest2 trial, comparing respectively, Amulet and WaveCrest® with the Watchman™ (both still in the recruitment phase), there are no randomized head-to-head trials comparing devices. Among the few registries published on the subject, there were no significant differences in success rates, complications, residual leak or late stroke when comparing the ACP to Amulet, 37 Watchman™ to ACP/Amulet 38 or Watchman™ to ACP/Amulet to LAmbre™, 39 suggesting that LAAO has a class effect, which does not depend on the device implanted, as long as the anatomical requirements are respected.…”
Section: Other Devicesmentioning
confidence: 93%